2019
DOI: 10.2298/jsc190125031s
|View full text |Cite
|
Sign up to set email alerts
|

Design of amino-functionalized chelated macroporous copolymer [poly(GMA-EDGMA)] for the sorption of Cu (II) ions

Abstract: Polymer-based, highly porous nanocomposites with functionalized ligands attached to the core structure are extremely efficient in the detection, removal and recovery of metals through the process of sorption. Quantumchemical models could be helpful for sorption process analyses. The sorption of Cu(II) ions by amino-functionalized chelating macroporous copolymers poly(GMA-co-EGDMA)-amine and sorption selectivity of the subject copolymers, ethylenediamine (en), diethylenetriamine (dien) and triethylenetetramine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Our previous works demonstrated that calculating the coordination bond energy for the chemisorption of metal ions on the polymer gives excellent agreement with the experimentally determined maximum sorption capacities [ 27 , 67 ]. Quantum chemical modeling of physisorption and calculation of the energy of non-covalent binding proved to help explain the binding mechanism of oxyanions to the polymer and the affinity of individual oxyanions for the polymer [ 21 ].…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Our previous works demonstrated that calculating the coordination bond energy for the chemisorption of metal ions on the polymer gives excellent agreement with the experimentally determined maximum sorption capacities [ 27 , 67 ]. Quantum chemical modeling of physisorption and calculation of the energy of non-covalent binding proved to help explain the binding mechanism of oxyanions to the polymer and the affinity of individual oxyanions for the polymer [ 21 ].…”
Section: Resultsmentioning
confidence: 53%
“…Cr(III) oxyanion, which is less toxic than Cr(VI), binds to N atoms directly by forming covalent bonds [ 66 ]. The sorption of Cu(II), Co(II), Cd(II), and Ni(II) ions by amino-functionalized chelating macroporous copolymers poly(GMA- co -EGDMA)-amine and sorption selectivity of the subject copolymers were successfully quantified experimentally and modeled by quantum chemical calculations [ 27 , 31 , 67 ]. According to these results, coordination of the diethylenetriamine group from Fe 3 O 4 @APTMS/PGME-deta to the Cr(III) ion can be expected.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of porous channels, their large surface area, and their unique chemical characteristics have led to the numerous potential applications of these porous materials [11][12][13][14][15][16][17]. Among them, the chelating polymer ligands based on glycidyl methacrylate (GMA) are very attractive, due to the presence of oxirane rings that can easily be transformed into various functional groups [18]. These materials have found applications in very diverse areas such as drug delivery [19], support for enzymes [20], and wastewater treatment [21], as well as catalysis [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that amino-functionalized GM-based copolymers possess a significant affinity for the sorption metal ions [7,8]. Moreover, these polymers are characterized by thermal and chemical stability [9,10].…”
Section: Introductionmentioning
confidence: 99%